(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aim: This study assesses the awareness, outlook & knowledge toward Pathological autopsy amongst medical students at tertiary care teaching center. Objectives: To assess medical student’s opinions, feelings and attitude towards autopsy and its importance in medical education. Material and Method: We conducted a study of 300 students studying 3rd and 5th semesters where they taught about the subject. We used questionnaire containing questions relating to autopsy to assess the awareness, outlook & knowledge towardPathological Autopsy. Results: Amongst the class of 300 students no statistically difference is observed in the views of male and female students on any item in the present study. Conclusion: The Forensic Medicine is important subject for medical profession. Teaching how to perform an autopsy is relevant and plays a positive role in medical education, and autopsy training from both theoretical and practical perspectives must be included in the forensic medicine curriculum. Medical institutes must take responsibility to increase awareness about the effect of media on medical education.